DEVELOPMENTAL STATE AND THE QUESTION OF ACCOUNTABILITY - Vusimuzi Gumbi; Keaobaka Tsholo (Universitas Nasional, 2023)
In South Africa, despite what appears to be a perfectly designed political system underpinned by the separation of powers, there seemingly is a lack of accountability of public officials that has its roots in the proportional representation (PR) electoral system. This study postulates that this has proven not to be effective in terms of accountability and oversight as far as the implementation of Chapter 13 of NDP and the broader objectives of South Africa’s development framework. The infamous Nkandla Projects and Parliamentary Inquiry into Eskom make for a worthy case study in this endeavour for at least one particular reason, these two case studies and all that came to encompass them extended over period adequately lengthy enough to check the consistency of Parliament and how South Africa’s electoral system leads to and breeds systemic political corruption that Parliament cannot decisively address and deal with. Furthermore, this study will argue how the Electoral Amendment Bill (B1-2022) could be effective in improving how MPs are delegated, held accountable and increasing state capacity through Parliamentary oversight.